Reporting and interpretation of SF-36 outcomes in randomised trials: systematic review. (12th January 2009) - Contopoulos-Ioannidis, Despina G; Karvouni, Anastasia; Kouri, Ioanna; Ioannidis, John P A
Abstract : Objective To determine how often health surveys and quality of life evaluations reach different conclusions from those of primary efficacy outcomes and whether discordant results make a difference in the interpretation of trial findings. Design Systematic review. Data sources PubMed, contact with authors for missing information, and author survey for unpublished SF-36 data. Study selection Randomised trials with SF-36 outcomes (the most extensively validated and used health survey instrument for appraising quality of life) that were published in 2005 in 22 journals with a high impact factor. Data extraction Analyses on the two composite and eight subdomain SF-36 scores that corresponded to the time and mode of analysis of the primary efficacy outcome. Results Of 1057 screened trials, 52 were identified as randomised trials with SF-36 results (66 separate comparisons). Only eight trials reported all 10 SF-36 scores in the published articles. For 21 of the 66 comparisons, SF-36 results were discordant for statistical significance compared with the results for primary efficacy outcomes. Of 17 statistically significant SF-36 scores where primary outcomes were not also statistically significant in the same direction, the magnitude of effect was small in six, moderate in six, large in three, and not reported in two. Authors modified the interpretation of study findings based on SF-36 results in only two of the 21 discordant cases. Among 100 additional randomly selected trials not reporting any SF-36 information, at least five had collected SF-36 data but only one had analysed it. Conclusions SF-36 measurements sometimes produce different results from those of the primary efficacy outcomes but rarely modify the overall interpretation of randomised trials. Quality of life and health related survey information should be utilised more systematically in randomised trials.